Petrografia dos calcários betuminosos neoproterozóicos do sul do cráton amazônico, região de Mirassol D'Oeste, MT - BRELAZ, Luciana Castro (2019)
The Neoproterozoic Guia Formation is inserted in the Araras Group and occurs along of Southern border of the Amazon craton and northern Paraguay belt. The basal portion of this formation, exposed in the Mirassol d´Oeste, State of Mato Grosso, is constituted of fine-grained bituminous limestone interbedded with laminas of bituminous shale, rich in pyrite. This basal Guia is the calcareous unit of Puga cap carbonate, characterized by anomalous features as calcite crusts and crystal fans, besides negative isotopic excursions of C and O. The petrographic study of this unit allowed identify two carbonatic microfacies: neomorphosed lime mudstone with terrigenous laminas and cementstone that confirm the previous interpretation of moderately deep waters and CaCO3 oversaturated carbonate platform. The lime mudstone is formed by xenotopic mosaic of microspar, with cloudy appearance and with laminas of terrigenous, mainly grains of quartz and, subordinately, feldspar and mica. The cementstone consists of calcite crusts, fibrous calcite and crystal fans, considered as aragonite pseudomorphs. Authigenic minerals represented by pyrite and pyrrhotite (?) are disseminated, genetically associated with organic matter thermal maturation, as well as the hydrocarbons altered to bitumen. The diagenetic sequence include: 1) neomorphism of micrite to microspars and calcitization of aragonite crystal fans; 2) organic matter maturation; 3) precipitation of authigenic minerals; 4) dolomitization of microfacies; 5) chemical compaction evidenced by stylolites; 6) fracturing; 7) cementation of fractures and pockets by spar calcite; 8) dolomite precipitation in fractures and pockets; 9) dissolution of calcite crystals and generation of secondary porosity; 10) bitumen migration; and 11) precipitation of euhedral dolomites in pockets filled by bitumen. The total organic matter content (TOC) above of 1% classify the Guia limestones as source rock and the type II of kerogen, obtained by pyrolisys/Rock-Eval analysis, confirms the high level of thermal evolution and some biodegradation. This research starts the digenetic understanding of Precambrian rock source in Brazil, with important implications to the hydrocarbons migration event of “Araras Petroliferous System”.